Effect and mechanism of rapamycin on proliferation and apoptosis of human lung cancer cells - Cao, Wenning; Ma, Lan (Cellular and Molecular Biology, 2020)
The purpose of this study was to investigate the effects of RAPA on the proliferation and the expression of p53, Bcl-2 and Bax proteins in cultured human small cell lung cancer (NCI-H446) cells, and to explore the possible mechanism of RAPA-treated NCI-H446 cells with different concentrations of RAPA-treated NCI-H446 cells. The proliferation of NCI-H446 cells in all groups was assayed by the CCK-8 method. FITC-Annexin V/PI double staining method was used to determine the apoptosis of NCI-H446 cells. The immunohistochemical SP method was used to detect the expression of p53, Bcl-2 and Bax. Expression of p53, Bcl-2 and Bax mRNA was detected by RT-PCR. The results showed that, after 48h treatment, the proliferation of NCI-H446 cells treated with 5ng/mL, 10ng/mL and 15ng/mL RAPA decreased significantly (P < 0.05) and the proliferation inhibition rate increased significantly (P < 0.05) compared with the control group, and the proliferation inhibition rate had a dose-dependent relationship with RAPA. Compared with the control group, the apoptosis rate of NCI-H446 cells treated with 5ng/mL, 10ng/mL and 15ng/mL RAPA increased significantly (P < 0.05), and there was a dose-dependent relationship between the apoptosis rate and RAPA. The expression of Bcl-2 protein and mRNA was higher in the control group, while the expression of p53 and Bax protein and mRNA was lower. The expression of Bcl-2 protein and mRNA decreased and the expression of p53 and Bax protein and mRNA increased gradually with the increase of concentration and the prolongation of action time in 5ng/mL, 10ng/mL and 15ng/mL RAPA groups. In the control group, the intracellular Ca2+ concentration was constant, and there was no significant change with time; while in the 5ng / mL, 10ng / mL, and 15ng / mL RAPA group, the intracellular Ca2+ concentration in the RAPA group increased significantly after 12 h of administration (P <0.05); After that, with the prolonged action time of the medicine, the intracellular Ca2+ concentration in the 5ng / mL, 10ng / mL, and 15ng / mL RAPA group decreased, but at 72h, the effect was 5ng / mL, 10ng / mL, and 15ng / mL RAPA. The intracellular Ca2+ fluorescence intensity in the group was still significantly higher than that in the control group (P <0.05). In conclusion, RAPA can induce apoptosis of NCI-H446 cells by down-regulating Bcl-2 gene expression, up-regulating P53 and Bax gene expression, and increasing intracellular Ca2+ concentration and its apoptosis induction effect have timeliness and dose-effect.